Optimization of Essential Oil Production from Cymbopogon citratus in Vietnam by Hydro-Distillation - Thi Cam Van Do; Thi Cuong Vu (Indonesian Journal of Chemistry, 2024)
Citral-rich lemongrass (Cymbopogon citratus) essential oils have been reported to exhibit anticancer, antimicrobial, antifungal, and antioxidant properties, leading to wide applications in the food industry, pharmaceuticals, cosmetics, perfumery markets, and pest inhibition. Vietnam has abundant lemongrass, which can be centralized to develop a lemongrass-based essential oil industry. In this work, essential oils were extracted from lemongrass harvested from the Bac Giang and Phu Yen provinces of Vietnam. The study aimed to investigate the influential factors, including distillation time, raw material size, water quality, and water-to-material ratio, to optimize oil production from C. citratus in a 10 L hydro-distillation boiler. The maximum oil yield was obtained under the optimal conditions: distillation time of 180 min, the plant material size of 2–3 mm, reverse osmosis (RO) and/or distilled water, and water-to-material ratio of 5/1 (mL/g). The maximum yields of lemongrass oil from Bac Giang and Phu Yen provinces were determined as 2.55 and 3.96 mL/kg, with corresponding citral contents analyzed of 45.5 and 68.1%, respectively. From the experimental data, a protocol for essential oil production from Vietnam’s C. citratus by the hydro-distillation technique was proposed.